1st international round robin test on safety characteristics of hybrid mixtures. (February 2023) - Spitzer, Stefan H.; Askar, Enis; Benke, Alexander; Cloney, Chris; D'Hyon, Sebastian; Dufaud, Olivier; Dyduch, Zdzislaw; Gabel, Dieter; Geoerg, Paul; Heilmann, Vanessa; Jankuj, Vojtech; Jian, Wang; et al.
Abstract: There is no applicable existing standard for the determination of safety characteristics for hybrid mixtures. While developing a new standard in a joint research project in Germany first results from parameter studies led to a standard procedure that can be adopted by laboratories that are already testing dusts in the so called 20L-sphere with as little additional effort as necessary. In fact, one of the main objectives of this research project was to keep modifications and adjustments from the generally accepted dust testing procedures as easy and minimal as possible so as to limit potential deviations from one laboratory to another. In this first round robin test on hybrid mixtures ever, with methane as gas component and a specific corn starch as dust sample, the practicality of the whole procedure, the scattering of the results and the deviation between the testing apparatuses is investigated. This paper summarizes the experimental procedure adopted and objectives of the first round-robin phase involving three of the four original German companies, plus volunteering laboratories from Australia, Belgium, Czech Republic, France, Poland and P.R. China. The results will have an impact on the new standard and may lead to robust data for later simulation purposes. Highlights: Comparison of measured data on hybrid mixtures between 11 facilities in 7 countries. Validation method for the determination of safety characteristics of hybrid mixtures. Proposal for a certificate for facilities, that measure safety characteristics of hybrid mixtures.